Neutron diffraction measurements of residual stress distribution in large zirconia based refractory bricks produced by electro-fusion and casting. Issue 5 (May 2017) - Örs, Taylan; Gouraud, Fanny; Guinebretière, René; Huger, Marc; Michel, Vincent; Castelnau, Olivier
Abstract: Electro-fusion and casting is used to produce large refractory bricks (∼250 kg) containing a high amount of ZrO2 . These bricks are used in glass-making furnaces where good mechanical performance is required at very high temperatures (>1500 °C). During the manufacturing procedure, they develop large residual stresses as a result of the cooling conditions and structural phase transformations they underwent. This leads to stress concentration and crack formation at different length scales. In order to characterize these phenomena, a 'multi-scale' analysis approach is under development, where different internal strain measurement methods are combined. In this approach we benefit from different gauge volumes provided by various diffraction methods, ranging from a few hundred nanometres to a few tens of millimetres. In the present paper, the results of neutron diffraction measurements on large ZrO2 blocks are given. These results show the level of internal strains at the millimetre scale, based on ( 3 ¯ 11 ) reflection of the monoclinic ZrO2 . Overall, a range of 0.025% tensile to 0.1% compressive strain was observed. Clear strain gradients were also visible, as larger values in the interior of the block were encountered.